Dielectric properties of semi-insulating Fe-doped InP in the terahertz spectral region - L. N. Alyabyeva; E. S. Zhukova; M. A. Belkin; B. P. Gorshunov (Scientific Reports, 2017)
Abstract We report the values and the spectral dependence of the real and imaginary parts of the dielectric permittivity of semi-insulating Fe-doped InP crystalline wafers in the 2–700 cm−1 (0.06–21 THz) spectral region at room temperature. The data shows a number of absorption bands that are assigned to one- and two-phonon and impurity-related absorption processes. Unlike the previous studies of undoped or low-doped InP material, our data unveil the dielectric properties of InP that are not screened by strong free-carrier absorption and will be useful for designing a wide variety of InP-based electronic and photonic devices operating in the terahertz spectral range.